Penggunaan Model Pembelajaran Kooperatif Tipe Think-Pair-Share (TPS) untuk Meningkatkan Kemampuan Komunikasi dan Disposisi Matematis Siswa di SMA Negeri 1 Bireuen - Marlina Marlina; Hajidin Hajidin; M. Ikhsan (Didaktik Matematika, 2014)
The use of cooperative learning model type of Think-Pair-Share is needed in order to helps students of learning to communicate mathematically as stated ideas, ask questions and respond question, and to developed students' mathematical disposition. This study aims to find out about increasing the ability of communication and mathematical disposition among students taught through cooperative learning model Think-Pair-Share with the students taught conventionally. This study uses a quantitative approach to the experimental method. The population in this study were all students of class XI SMA Negeri 1 Bireuen and take samples of the two classes (class experimental and control) with the selection of the sample through purposive sampling technique. Collecting data in this study using two different tests and instrument the nontes. Instrument tests the ability of mathematical communication and mathematical disposition nontes include scale and observation sheets. To look at the differences increased communication ability and mathematical disposition on the experimental and control classes using the Mann Whitney test with a significance level of 0.05, and to see the interaction between learning models and the grouping of students to increase communication ability and dispositions mathematically using ANOVA two lanes. Statistical test results were analyzed using SPSS 17.0. Based on the results: (1) Increase the ability of mathematical communication between students taught through cooperative learning model TPS better than students taught conventionally based on: 1) The whole student, and 2) grouping of students. (2) There is a model of the interaction between learning and grouping of students to increase mathematical communication ability. (3) Improved mathematical dispositions among students taught through cooperative learning model TPS better than students taught conventionally based on: 1) The whole student, and 2) grouping of students. (4) There is a model of the interaction between learning and grouping of students to increase mathematical disposition. (5) The response of students towards learning math using cooperative learning model TPS is positive.